CYCLO-(TRP-PHE) DIKETOPIPERAZINES FROM THE ENDOPHYTIC FUNGUS Aspergillus versicolor ISOLATED FROM Piper aduncum# - Gubiani, Juliana R. [UNESP]; Teles, Helder L.; Silva, Geraldo H.; Young, Maria Claudia M.; Pereira, Jose O.; Bolzani, Vanderlan S. [UNESP]; Araujo, Angela R. [UNESP] (Soc Brasileira Quimica, 2017)
Six known compounds, three peptide derivatives: cyclo-(tryptophyl-phenylalanyl) (2), diketopiperazine dimer WIN 64821 (3) and 3-hydroxy-15H-tryptophenaline (4), one adenine derivative: 2-hydroxy-6-N-isopentenyl-adenine (5), one phtalide derivative: 4-methoxyphtalide (1) and one benzoic acid derivative: 3-hydroxy-4-(1-hydroxy-1,5-dimethyl-hexyl) benzoic acid (6), were isolated from the ethyl acetate extract of the endophytic fungus Aspergillus versicolor associated with the Piper aduncum plant. Their structures were determined on the basis of detailed interpretation of 1 D and 2D NMR spectra and in comparison with works reported in the literature. This paper, in effect, deals with the first report of these compounds in A. versicolor.
Keywords: cyclo-(Trp-Phe) diketopiperazines; endophytic fungus; Aspergillus versicolor; Piper aduncum.